Empowering Parents Through Implementing the Traditional Game’s Guidebook for Early Childhood Development - Muhammad Yusuf Alfayed; Serafin Wisni Septiarti (STAI Hubbulwathan Duri, 2025)
Traditional games are culturally rich educational tools that support children's cognitive and social development. However, the increasing dominance of modern technology and online games has led children to neglect these heritage-based activities. To address this issue, this study aimed to develop a guidebook to help parents reintroduce traditional games to early childhood in a structured and engaging way. This research employed the Research and Development (RD) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The study was conducted at Posyandu Pandan Wangi, Pandan Lagan Village, Jambi Province. The guidebook was validated through product trials involving 1 material expert, 1 media expert, 5 posyandu cadres, and 30 parents. Validation results showed that the guidebook received high feasibility scores: 48 from the material expert, 68 from the media expert, and 97 from the posyandu cadres, all classified as “very feasible.” Additionally, an effectiveness test conducted with parents showed a significant improvement in knowledge about traditional games, with an N-Gain score of 89.67%, indicating a high level of effectiveness (75%). The study concludes that the guidebook is both feasible and effective as a learning medium for parents to promote traditional games to young children. Future applications of this guidebook in broader communities are recommended to help preserve cultural heritage and encourage educational play among children.